Influence of the Method of Data Collection on the Documentation of Blood-pressure Readings with an Anesthesia Information Management System (AIMS) - Benson, M.; Junger, A.; Quinzio, L.; Fuchs, C.; Michel, A.; Sciuk, G.; Marquardt, K.; Dudeck, J.; Hempelmann, G. (Methods of Information in Medicine, 2001)
The influence of methods for record keeping on the documentation of vital signs was assessed for the Anesthesia Information Management System (AIMS) NarkoData. We compared manually entered blood-pressure readings with automatically collected data. These data were stored in a database and subsequently evaluated and analyzed. The data sets were split into two groups, ”manual“ and ”automatic“. We evaluated the effect of automatic data collection on the incidence of corrected data, data validity and data variation. Blood-pressure readings of 37,726 data sets were analyzed. We could assess that the method of documentation did influence the data quality. It could not be assessed whether the incorrectness of data during automatic data gathering was caused by artefacts or by the anesthesiologist.
Keywords: Automatic Record Keeping; Anesthesia Information Management System; Documentation; Quality Assurance